2017
DOI: 10.1007/978-3-319-68548-9_40
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Based Pupillometry: An Empirical Evaluation of Accuracy and Safety

Abstract: The Pupillary Light Reflex (PLR) is an involuntary reflex that changes the size of the pupil in response to varying light conditions. PLR analysis is widely employed in the evaluation of several neurological and ocular conditions and quantitative pupillometry requires the use of expensive ophthalmic instruments. In this paper, we describe an empirical evaluation we performed on the use of a commercially available smartphone (Apple iPhone 6s) to make quantitative measurements of PLR. Measurements were made with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Several groups have described the use of the unmodified rear-facing camera and visible light spectrum from light emitting diode (LED) flashlight of smartphones for pupillography and pupillometry (Table 3). [4][5][6][7][8][9][10][11][12] Some have described momentary illumination of the pupils with flashlights to capture pupillary images during different stages of PLR, while others captured pupillography videos during continuous LED flashlight illumination of the pupils. 4,8-10 Shin et al 4 introduced a smartphone application that acquires five sequential images using the rear-facing camera and flashlight to illuminate the pupil during PLR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have described the use of the unmodified rear-facing camera and visible light spectrum from light emitting diode (LED) flashlight of smartphones for pupillography and pupillometry (Table 3). [4][5][6][7][8][9][10][11][12] Some have described momentary illumination of the pupils with flashlights to capture pupillary images during different stages of PLR, while others captured pupillography videos during continuous LED flashlight illumination of the pupils. 4,8-10 Shin et al 4 introduced a smartphone application that acquires five sequential images using the rear-facing camera and flashlight to illuminate the pupil during PLR.…”
Section: Discussionmentioning
confidence: 99%
“…9 McKay et al compared the commercially available Brightlamp iPhone application (BL; Brightlamp Inc., Indianapolis, IN, USA) with a portable infrared pupillometer and demonstrated poor reproducibility of the application. 10 Calandra et al 12 reported that the Sober-Eye application (SOBER-EYE Inc., Menlo Park -CA, USA), 12 designed to self-assess pupillary reaction to a smartphone light flash as a measure of level of impairment from drugs or alcohol, is highly correlated with manual measurements. 9 Typically, non-infrared methods of pupillography (i.e., those reliant on visible light) are limited in evaluation of the dim/dilating states of the pupil, particularly in patients with dark irides, and this characteristic limits the clinical application of these devices.…”
mentioning
confidence: 99%
“…The potential phototoxic effect of smartphone retinal photography has been studied on a limited number of phones in a few prior reports [ 13 , 15 - 17 ]. With the ongoing advancements in smartphone cameras and their associated brighter LED flashlights, studying of the safety of newer generations of smartphones and previously untested smartphone versions are indicated [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been some concerns regarding the safety of the smartphone´s flashlight on the neurosensory retina and RPE [ 13 , 15 ]. A few older versions of smartphones´ flashlights had been tested for their safety for indirect retinal photography in a few prior reports, most recently in 2018 [ 13 , 15 - 17 ]. With the ongoing advancements in smartphone cameras and their associated brighter LED flashlights, studying the safety of newer generations of smartphones and previously untested smartphone versions are indicated [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 Previous studies have demonstrated that the use of a smartphone's flashlight does not harm the human eye, and its potential hazard is far below the constraints of international safety standards. 7 Recently, in a controlled study, an iPhone-based pupillometer established a statistically significant correlation with the infrared pupillometry method. 8 The aim of this study is the introduction and standardization of a pupil examination method using an android mobile pupillography app ("Doctor kit") developed in the Faculty of medicine of the Autonomous University of San Luis Potosi, in cooperation with Discomp Mobile inc. (Ing.…”
Section: Introductionmentioning
confidence: 99%